Association of Yokohama System for Reporting Breast Lesions with BI-RADS - Thapa, Rojin; Khadka, Pooja; Gautam, Dipti; KC, Shiva Raj (Nepalese Medical Journal, 2025)
Introduction: The newly developed International Academy of Cytology Yokohama System standardizes the reporting system, fostering uniformity in reporting practices. The study aimed to assess the diagnostic utility of the International Academy of Cytology Yokohama System for Reporting Breast Fine Needle Aspiration Biopsy Cytopathology, and comparison with Breast Imaging-Reporting and Data System. Materials and Methods: A prospective cross-sectional observational study was conducted, spanning a one-year period. The study focused on patients with breast lesions who were undergoing Fine Needle Aspiration Cytology and had ultrasonography. The association of the Yokohama system and Breast Imaging-Reporting and Data System, with calculation of statistical measures; sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy was done. Results: The study included 109 patients with breast lesions, comprising 101 females (92.7%) and 8 males (7.3%). Results showed a strong association between Yokohama categories and Breast Imaging-Reporting and Data System, with high sensitivity (94.44%), specificity (97.70%), positive predictive value (89.47%), negative predictive value (98.83%), and overall accuracy (97.14%). The p-value calculated was <0.05 and was statistically significant. Conclusions: This study successfully implemented a standardized reporting system for all breast Fine Needle Aspiration Cytology cases, utilizing the International Academy of Cytology Yokohama System for Reporting Breast Fine Needle Aspiration Biopsy Cytopathology at Patan Academy of Health Sciences. The findings of the study demonstrated consistency with Ultrasonography Breast Imaging-Reporting and Data System, thereby contributing valuable insights for patient management.